Musical Composition of Introverts dan Ekstroverts’ Extramusical Idea - Mohamad Rohmatullah (Institut Seni Indonesia Denpasar, 2020)
Purpose: Humans have different personalities, namely introverts and extroverts. Program music is one of the compositional techniques whose purpose is to describe something in the creation of music through the analogy of meaning. Research methods: This creation research uses the Practice-Led Research method. Data obtained through a literature study approach, then the data is associated with music through an analogy process. Results and discussion: The creative process in creating music is very diverse, one of which is through extra-musical ideas. In the realm of music creation other disciplines can be used as music creation ideas. Psychology and music can be related through listening and feeling. The musical works created are vocal and piano works about introverts and extroverts. Implication: The implications of this research creation are expected to trigger the idea of creating music more broadly, especially across scientific disciplines.